1989
DOI: 10.1093/infdis/159.6.1073
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ciprofloxacin and a Monoclonal Antibody to Lipopolysaccharide Protect Leukopenic Rats from Lethal Infection with Pseudomonas aeruginosa

Abstract: To study the treatment of infection with Pseudomonas aeruginosa, a leukopenic rat model was developed that closely mimics the pathogenesis of Pseudomonas infection in man. This model achieved approximately 90% mortality within 10 d of infection. Pseudomonas organisms were inconsistently shed from the feces despite gastrointestinal colonization (9 fecal v. 23 cecal cultures positive for challenge strain in 28 rats). Treatment of rats with oral ciprofloxacin at 40 mg/kg afforded complete protection. A suboptimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Anderson and Montie (1,2) demonstrated that this activity is complement independent (1) and that only 20% of internalized bacteria are killed when bacteria are opsonized with antiflagella antiserum (2). Those Recent reports have demonstrated additive effects of a murine LPS-reactive MAb administered in combination with oral quinolone derivatives in neutropenic animal models of Pseudomonas infections (5,6,20). In the present study, antiflagella MAb interacted additively with the quinolone antibiotic sparfloxacin, as reflected by the enhanced antibacterial activity in infected lung tissue and reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson and Montie (1,2) demonstrated that this activity is complement independent (1) and that only 20% of internalized bacteria are killed when bacteria are opsonized with antiflagella antiserum (2). Those Recent reports have demonstrated additive effects of a murine LPS-reactive MAb administered in combination with oral quinolone derivatives in neutropenic animal models of Pseudomonas infections (5,6,20). In the present study, antiflagella MAb interacted additively with the quinolone antibiotic sparfloxacin, as reflected by the enhanced antibacterial activity in infected lung tissue and reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, after obtaining the original J5 strain from Elizabeth Ziegler, we immunized rabbits with a heat-killed J5 mutant vaccine, purified the serum antibodies first over a protein A column to isolate the IgG and then passed the protein A eluate (IgG) over a J5 LPS affinity column 53 . These IgG fractions (total IgG antibody, non-J5 LPS IgG [affinity column pass-through] and J5 LPS-specific IgG [affinity column eluate]) were evaluated for levels to J5 LPS, lipid A and to P. aeruginosa LPS from a strain to be used in a neutropenic rat model of experimental sepsis 54 (Table 2). Rats were administered a clinical isolate of P. aeruginosa by gavage and temperature monitored.…”
Section: Detoxified J5 Lps Vaccine For the Prevention And Treatment Omentioning
confidence: 99%
“…The LPS of P. ne)-tigirzosn is a potent immunogen, and antibody directed against its 0-polysaccharide side chain promotes opsonophagocytic killing and protection in experimental infection [207]. The LPS of P. ne)-tigirzosn is a potent immunogen, and antibody directed against its 0-polysaccharide side chain promotes opsonophagocytic killing and protection in experimental infection [207].…”
Section: Immunological Approaches To Prophylaxis and Therapymentioning
confidence: 99%